2016
DOI: 10.3390/ijms17091420
|View full text |Cite
|
Sign up to set email alerts
|

Cleome rutidosperma and Euphorbia thymifolia Suppress Inflammatory Response via Upregulation of Phase II Enzymes and Modulation of NF-κB and JNK Activation in LPS-Stimulated BV2 Microglia

Abstract: Cleome rutidosperma DC. and Euphorbia thymifolia L. are herbal medicines used in traditional Indian and Chinese medicine to treat various illnesses. Reports document that they have antioxidant and anti-inflammatory activities; nonetheless, the molecular mechanisms involved in their anti-inflammatory actions have not yet been elucidated. The anti-neuroinflammatory activities and underlying mechanisms of ethanol extracts of Cleome rutidosperma (CR) and Euphorbia thymifolia (ET) were studied using lipopolysacchar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…Several plant derived natural products were shown to exert anti-inflammatory effects via inhibition of the NF-κB/iNOS pathway mediated NO production [33,[62][63][64][65]. Therefore, the screened candidate constituents may act by this mechanism and may contribute to the NO production inhibition effect by the extracts.…”
Section: Discussionmentioning
confidence: 99%
“…Several plant derived natural products were shown to exert anti-inflammatory effects via inhibition of the NF-κB/iNOS pathway mediated NO production [33,[62][63][64][65]. Therefore, the screened candidate constituents may act by this mechanism and may contribute to the NO production inhibition effect by the extracts.…”
Section: Discussionmentioning
confidence: 99%
“…Small molecules that activate Nrf2 signaling are under active study for their potential to become anti-inflammatory and cancer preventive agents ( Wu et al, 2010 ). Plants are rich sources of Nrf2 activing phytochemicals; therefore, development of anti-inflammatory Nrf2 activators from plant extracts has attracted attention in biomedical field ( Ahmed et al, 2017 ; Ding et al, 2016 ; Wu et al, 2015 , 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…As many tumor promoters can cause inflammatory symptoms, the inhibitory effect against TPA-induced ear inflammation has a close correlation with the inhibition of TPA-induced tumor promotion in a two-stage carcinogenesis. Thus, we chose the medicinal plants of the genus Euphorbia (Euphorbiaceae) which contained triterpenoids to study their chemical constituents and pharmacological activity [ 11 ]. We found that the lanostane-type triterpenes of E. kansui markedly possessed the inhibitory activity against TPA-induced inflammation, and the predominant triterpene in this plant, euphol, significantly inhibited the tumor-promoting activity induced by TPA [ 12 ].…”
Section: Introductionmentioning
confidence: 99%